ANALISIS KOMPARASI KEPUASAN KONSUMEN COFFEE SHOP DI YOGYAKARTA (JASEP, 2015)
This research aims to compare between two coffee shops in Yogyakarta which researcher analyze the differences of product and service quality attributes and consumer satisfaction level of each coffee shop. This research using survey method with quantitative data, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) by 50 respondents from each coffee shop. According to consumer assessment, there is five sequence of product and service quality attributes that satisfy consumers at coffee shop A are: (1) Taste; (2) Consistency of taste, flavor and portion (3) Hygiene of beverage; (4) Accessibility of coffee shop; (5) Product flavor. Meanwhile, consumer at coffee shop B assess that five sequence of product and service quality attributes that satisfy consumers are: (1) The friendliness of waiters; (2) Waiter’s responses; (3) Taste (4) Hygiene of beverage; (5) Proper price offered. The result showed that customer satisfaction of coffee shop A higher than coffee shop B, that shown by the CSI of coffee shop A is 81 %, while coffee shop B is 78 Generally, consumer satisfaction level of coffee shop in Yogyakarta is good ("satisfy").